The effect of 19 years of restoration managements on forage quality and herbage‐soil relationships within improved upland grassland. (13th July 2022) - Kajzrová, Klára; Kassahun, Teowdroes; Pavlů, Lenka; Pavlů, Vilém V.; Fraser, Mariecia D.
Abstract: Restoration managements based on extensification strategies are commonly used to improve biodiversity on formerly improved grasslands. In this study the long‐term effects of six different restoration management regimes (extensive sheep grazing only, hay cutting only, hay cutting followed by aftermath extensive grazing; each with and without lime application) on forage quality, and soil/herbage/sward characteristics relationships were determined and compared with a conventionally fertilized, limed and extensively grazed control. Restoration managements incorporating cutting resulted in higher forage quality than forage from grazed‐only treatments; the latter featuring only a few forb species and large proportion of ungrazed matured grasses plus dead biomass. Concentrations of crude protein, neutral detergent fibre and K in the herbage were negatively correlated with cover of forbs and total number of plant species, whereas in vitro organic matter digestibility, and concentrations of water‐soluble carbohydrates, Ca, Mg, and Na were correlated positively. In contrast, concentrations of Ca, Mg, and Na were negatively correlated with the total cover of graminoids and dry matter standing biomass. Regardless of management treatment the forage was generally suitable only for sheep or beef cattle feeding. A positive relationship between P and K concentration in the soil and in the herbage was recorded. No effect of previous liming on forage quality was found. Overall, this study found introducing long‐term restoration managements to support biodiversity by postponing the timing of the first defoliation by cutting to mid growing season did not deteriorate forage quality in comparison with continual extensive sheep grazing in improved upland grassland.